2019
DOI: 10.5902/1980509832280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cover on the development and production of secondary compounds of <i>Maytenus ilicifolia</i> and <i>Ilex paraguariensis</i> in agroforestry systems

Abstract: Effect of cover on the development and production of secondary compounds of Maytenus ilicifolia and Ilex paraguariensis in agroforestry systemsEfeito da cobertura do dossel no desenvolvimento e produção de compostos secundários de Maytenus ilicifolia e Ilex paraguariensis em sistemas agroflorestais AbstractThe Midwest regions of Santa Catarina state, in Brazil, include a great diversity of forest essences with medicinal application; however, many of these resources are poorly exploited or managed in an extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
2
1
2
Order By: Relevance
“…For Rocha et al (2014), full sunlight was also the most appropriate management for the production of M. ilicifolia leaves, influencing the sprouting capacity of population after partial pruning. However, differing from our results, Borges et al (2019) found no differences for height, stem diameter, and biomass production of M. ilicifolia plants with different canopy cover (0% -60%) in two agroforestry systems in the State of Santa Catarina, Brazil, during the first three years after planting.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For Rocha et al (2014), full sunlight was also the most appropriate management for the production of M. ilicifolia leaves, influencing the sprouting capacity of population after partial pruning. However, differing from our results, Borges et al (2019) found no differences for height, stem diameter, and biomass production of M. ilicifolia plants with different canopy cover (0% -60%) in two agroforestry systems in the State of Santa Catarina, Brazil, during the first three years after planting.…”
Section: Discussioncontrasting
confidence: 99%
“…The species presents significant environmental plasticity. It grows under different edaphic conditions, soil hydromorphic regimes, and luminosity, occurring naturally in full sun and diffuse light environments (Radomski & Bull, 2010;Borges et al, 2019). For adult plants of M. ilicifolia, shading condition affects biomass production, specific leaf area, leaf nutrient concentrations and polyphenols contents (Radomski et al, 2004;Radomski & Bull, 2010;Rocha et al, 2014;Borges et al, 2019); thus, shading seems to be an important factor for the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a densidade de 4.000 plantas por hectare, no espaçamento de 1,0 m na linha e 2,5 m entre linhas é considerada apropriada (MAGALHÃES, 2002). Consideramos que outras formas de cultivo, como os policultivos ou sistemas agroflorestais, são bastante apropriados para a produção da espécie (PASTUR et al, 2012;BIASI et al, 2017;BORGES et al 2019;STEENBOCK et al, 2020), podendo ser, inclusive, utilizada na restauração ecológica de áreas de preservação permanentes (APPs) ou reservas legais (RLs) (DALPIZOL et al, 2021), no entanto, são ainda incipientes as experiências com o cultivo da espinheira-santa nestas formas de cultivo. Borges et al (2019) registram uma diminuição de compostos de interesse com o aumento do sombreamento, o que deve ser considerado em sistemas de policultivo.…”
Section: Fitotecniaunclassified
“…Sua origem é antiga, assim como sua prática, e muitos cientistas reconhecem como ela auxilia no desenvolvimento dos povos (ALBUQUERQUE et al, 2008;MEDEIROS et al, 2011). Assim, em face à crise ambiental que presenciamos, é de suma importância que possamos analisar o desenvolvimento humano sem deixar de lado a conservação de ecossistemas naturais e a promoção de serviços ambientais e ecossistêmicos (BROOKS et al, 2006;TELLO;CASTILHO, 2013;LUEDLING et al, 2014;ANDERSON et al, 2020;STEENBOCK et al, 2020).…”
Section: Introductionunclassified